Legal Analysis of Gorontalo Urban Drainage Development: Social Justice Perspective - Dian Ekawaty Ismail; Mellisa Towadi; Sarlin Hiola (Universitas Kuningan, 2020)
Justice is one of the main basic ideas in a rule or law. A rule is not considered as a law if it does not provide a sense of justice to the subject it governs. The aim of this article is to analyze the context of social justice on the effectiveness of urban drainage construction facilities system in the cities. This study used an empirical-juridical method based on the Minister of Public Works Regulation Number 12 of 2014, the implementation of Urban Drainage. The result of data analysis showed since the planning stage, the implementation of each infrastructure development in the city of Gorontalo continually refers to the spatial planning map and collaborates with the associations engaged in the environmental sector so that it reaches the development and control processes. In this case, an infrastructure of the drainage facility does not violate its designated zone. Yet, there are several zones whose utilization is not in accordance with their designation. Thus, the problem collides with the fulfillment of social justice which affects the implementation of drainage facilities construction.Keadilan merupakan salah satu ide dasar pokok dalam sebuah peraturan atau hukum. Sebuah peraturan bukanlah hukum jika tidak memberi rasa keadilan terhadap subjek yang diaturnya. Tujuan artikel ini untuk menganalisis konteks keadilan sosial pada efektivitas pembangunan fasilitas sistem drainase perkotaan di kota dengan menggunakan metode yuridis empiris berdasarkan Peraturan Menteri Pekerjaan Umum Nomor 12 Tahun 2014 tentang Penyelenggaraan Drainase Perkotaan. Hasil penelitian Analisis data menunjukkan bahwa setiap pelaksanaan pembangunan infrastruktur di kota Gorontalo sejak perencanaannya selalu mengacu pada peta penataan ruang wilayah dan melakukan kerjasama dengan asosiasi yang bergerak di bidang lingkungan hidup sehingga sampai pada proses pembangunan dan pengendalian, sebuah infrastruktur dalam hal ini fasilitas drainase tidak menyalahi zona peruntukkannya. Meskipun masih terdapat beberapa zona yang pemanfaatannya tidak sesuai peruntukkannya sehingga permasalahan terbentur pada pemenuhan keadilan sosial yang mempengaruhi pelaksanaan pembangunan fasilitas